Preparation method of zinc-based composite piezoelectric catalyst and application of zinc-based composite piezoelectric catalyst in piezoelectric catalytic hydrogen production
The zinc oxide-zinc sulfide composite catalyst was prepared by microwave-oil bath method, which solved the problems of high catalyst cost and strong light dependence in the prior art, and achieved efficient piezoelectric catalytic hydrogen evolution and good cycle stability.
Patent Information
- Application Number
- CN202411847087.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-25
AI Technical Summary
The existing electrocatalytic and photocatalytic decomposition of water to produce hydrogen gas has problems such as high prices of precious metal catalysts, limited scarcity and light dependence are limited by time and region, while piezoelectric catalytic technology lacks efficient catalysts.
The zinc oxide-zinc sulfide composite catalyst is prepared by microwave-oil bath combination method, and the piezoelectric properties of the catalyst are improved through chemical bonding, and used in piezoelectric catalytic hydrogen production.
Efficient piezoelectric catalytic hydrogen evolution was achieved, with the hydrogen evolution efficiency reaching 1802 μmol/g in 5 hours, and the catalyst had excellent cycle stability, and the average yield decreased by only 12.2% after 50 hours.
Smart Images

Figure CN119680577A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of piezoelectric catalytic hydrogen production, and in particular to a method for preparing a zinc-based composite piezoelectric catalyst and its application in piezoelectric catalytic hydrogen production. Background Art
[0002] The rapid growth of the world's population, industrial development and continued dependence on fossil fuels have directly led to the deterioration of environmental quality and the global energy crisis. In order to overcome these serious threats, new energy solutions are moving towards a sustainable economy and a safe lifestyle, such as relying on renewable energy sources that have less impact on the environment. In this sense, the clean energy industry is turning to hydrogen as a potential alternative to fossil fuels because its combustion process can produce up to 1.4×105kJ / kg of energy, while its only byproduct is water.
[0003] With the advancement of science and technology, various catalytic technologies are being developed simultaneously to exploit various forms of energy, especially the great potential of mechanical vibration and temperature fluctuation, which have been shown to trigger various catalytic reactions by adopting piezoelectric and pyroelectric materials. These methods provide promising solutions to energy dilemmas and environmental challenges by utilizing natural energy (such as wind energy, wave oscillations, water flow, day and night temperature changes, industrial waste heat, etc.).
[0004] The piezoelectric effect can convert mechanical vibrations on the surface of piezoelectric materials into electrical energy. When the piezoelectric or pyroelectric effect is coupled with the electrochemical redox process of water, the catalytic process driven by acoustic vibration or temperature is activated. Whether it is piezoelectric or thermal catalysis, the main research goal is to develop piezoelectric or thermal catalysts that are highly sensitive to mechanical and temperature changes to ensure the effective initiation of related reactions. The relevant catalysts should also have a large number of active sites and a high concentration of charge carriers, which play a vital role in electrochemical reactions. Meeting these requirements will be an important milestone in the field of piezoelectric and pyroelectric catalysis.
[0005] At present, the main means of splitting water to produce hydrogen are electrocatalysis and photocatalysis. Among them, electrocatalysis technology is the most mature, but the energy source of its catalytic reaction must rely on external electricity. Precious metals such as platinum and palladium, as commonly used electrocatalysts, are limited in large-scale application of electrocatalytic water splitting due to their high prices and scarcity. Research on photocatalytic water splitting to produce hydrogen has also made significant progress, but photocatalysis has a fatal drawback, that is, the redox reaction must occur under sufficient light conditions, which makes photocatalytic water splitting to produce hydrogen greatly limited in time and region. Piezoelectric catalysis is completely unrestricted by sunlight, and the energy sources it requires are rich and diverse, including vibration, water flow, friction, tidal energy, and environmentally friendly energy such as human activities. Summary of the invention
[0006] The purpose of the present invention is to solve the problems in the prior art and to provide a method for preparing a zinc-based composite piezoelectric catalyst and its application in piezoelectric catalytic hydrogen production.
[0007] In order to achieve the above object, the technical solution of the present invention is:
[0008] A method for preparing a zinc-based composite piezoelectric catalyst comprises the following steps:
[0009] Step 1: Preparation of ZnO nanorods
[0010] 1) adding zinc acetate dihydrate into deionized water and stirring to obtain a solution A with a concentration of 0.1 to 0.3 mol / L;
[0011] 2) Dissolve hexadecyl dimethyl ammonium bromide (CTAB) in water to obtain a concentration of (2-4)×10 -3 mol / L solution B;
[0012] 3) Mix solution A and solution B, and stir them thoroughly at room temperature to obtain solution C;
[0013] 4) transferring solution C to a microwave reactor with a polytetrafluoroethylene liner for microwave reaction at a reaction temperature of 140-170° C. for a reaction time of 30-60 min. After the reaction is completed, transferring the white product (i.e., zinc oxide) in the reactor to a centrifuge tube, washing and centrifuging with deionized water and anhydrous ethanol for multiple times, and then drying the product in a drying oven to finally obtain zinc oxide nanorods;
[0014] Step 2: Preparation of zinc oxide-zinc sulfide composite piezoelectric catalyst
[0015] 1) adding the zinc oxide nanorods prepared above into a 0.05 M thiourea solution and stirring to obtain a white suspension;
[0016] 2) Transfer the white suspension to an oil bath and heat with stirring at a temperature of 60-80°C and stir thoroughly;
[0017] 3) After the reaction is completed, the mixture is cooled and post-treated to finally obtain a zinc oxide-zinc sulfide composite piezoelectric catalyst.
[0018] The post-treatment includes multiple centrifugal washings using deionized water and anhydrous ethanol respectively, and after the centrifugation, the obtained samples are placed in a constant temperature drying oven for drying.
[0019] An application of a zinc-based composite piezoelectric catalyst in piezoelectric catalytic hydrogen production, characterized in that it comprises the following steps:
[0020] The zinc oxide-zinc sulfide composite catalyst was placed in a two-way sealed sampling bottle containing a hole capture agent and deionized water, and exhaust treatment was performed for more than 30 minutes. Then, the reactor was placed in an ultrasonic cleaner to perform piezoelectric hydrogen evolution reaction.
[0021] The hole capture agent is Na2S / Na2SO3 solution, lactic acid, triethanolamine or methanol.
[0022] The power of the ultrasonic cleaner is 100W-140W.
[0023] The exhaust treatment uses inert gas, such as nitrogen, argon, etc.
[0024] The beneficial effects of the present invention are:
[0025] 1. The microwave-oil bath combined method adopted by the present invention can prepare the zinc oxide-zinc sulfide composite catalyst more quickly and conveniently. Compared with the hydrothermal method in an oven, the microwave method has a strong ability to penetrate objects, so the objects can quickly and evenly absorb microwaves and spread throughout the entire object, which makes the heating process fast and stable, and is therefore more time-saving and efficient; the use of an oil bath to partially vulcanize zinc oxide avoids the high-temperature reaction of the hydrothermal method and has lower costs.
[0026] 2. In the zinc oxide-zinc sulfide composite catalyst, zinc oxide and zinc sulfide are chemically bonded rather than simply physically attached, which allows charge transfer to occur between zinc oxide and zinc sulfide, greatly suppressing the coupling of electron-hole pairs on the surface of the material, and effectively improving the piezoelectric catalytic hydrogen evolution performance of the zinc oxide-zinc sulfide composite material. Experimental results show that the 5-hour piezoelectric catalytic hydrogen evolution efficiency of the zinc oxide-zinc sulfide composite material can reach 1802μmol / g.
[0027] 3. The zinc oxide-zinc sulfide composite piezoelectric catalyst of the present invention has excellent cycle stability. After 50 hours of circulation, the average yield of its piezoelectric catalytic hydrogen evolution only decreases by 12.2% and tends to be stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope image of the composite catalyst of the present invention. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below in conjunction with embodiments.
[0030] Example 1
[0031] Preparation of zinc oxide nanorods: 4 mmol of zinc acetate dihydrate was added to 15 mL of deionized water and stirred to obtain solution A;
[0032] Dissolve 0.04 mmol of hexadecyldimethylammonium bromide (CTAB) in 15 mL of deionized water to obtain solution B;
[0033] Solution A and solution B were mixed and stirred at room temperature for 60 min. The mixture was stirred thoroughly to obtain solution C.
[0034] Solution C was completely transferred to a microwave reactor with a polytetrafluoroethylene liner for microwave reaction at a reaction temperature of 160°C for 45 minutes. After the reaction was completed, the white product in the reactor was transferred to a centrifuge tube, washed and centrifuged with deionized water and anhydrous ethanol for multiple times, and then the product was dried in a drying oven at 60°C to finally obtain zinc oxide nanorods.
[0035] Preparation of zinc oxide-zinc sulfide composite piezoelectric catalyst: The zinc oxide nanorods (100 mg) prepared above were added to 50 mL of thiourea solution (0.05 M) and stirred to obtain a white suspension;
[0036] The white suspension was transferred to a 70°C oil bath and heated with stirring for 10 h;
[0037] After the reaction is completed, the sample is cooled and washed by centrifugation multiple times with deionized water and anhydrous ethanol. After the centrifugation, the sample is placed in a 70°C constant temperature drying oven and dried overnight to finally obtain a zinc oxide-zinc sulfide composite piezoelectric catalyst.
[0038] The applications of piezoelectric catalytic hydrogen production are as follows:
[0039] Take 100 mg of zinc oxide-zinc sulfide composite catalyst and put it into a two-way closed sampling bottle containing Na2S / Na2SO3 solution and deionized water. Use nitrogen to exhaust the reactor for 30 minutes. Then, place the reactor in an ultrasonic cleaner (40kHz, 100W) for piezoelectric hydrogen evolution reaction, and detect the hydrogen content in the closed reactor every hour.
[0040] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1719 μmol / g.
[0041] Example 2
[0042] Preparation of zinc oxide nanorods: 1.5 mmol zinc acetate dihydrate was added to 15 mL deionized water and stirred to obtain solution A;
[0043] Dissolve 0.03 mmol of hexadecyldimethylammonium bromide (CTAB) in 15 mL of deionized water to obtain solution B;
[0044] Solution A and solution B were mixed and stirred at room temperature for 60 min to obtain solution C;
[0045] Solution C was completely transferred to a microwave reactor with a polytetrafluoroethylene liner for microwave reaction at a reaction temperature of 140°C for 60 minutes. After the reaction was completed, the white product in the reactor was transferred to a centrifuge tube, washed and centrifuged with deionized water and anhydrous ethanol for multiple times, and then the product was dried in a drying oven at 60°C overnight to finally obtain zinc oxide nanorods.
[0046] The preparation of the zinc oxide-zinc sulfide composite piezoelectric catalyst is the same as the steps in Example 1.
[0047] The piezoelectric catalytic hydrogen production step is the same as that in Example 1. The gas chromatography test results show that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst is 1538 μmol / g.
[0048] Example 3
[0049] Preparation of zinc oxide nanorods: 4.5 mmol zinc acetate dihydrate was added to 15 mL deionized water and stirred to obtain solution A;
[0050] Dissolve 0.06 mmol of hexadecyldimethylammonium bromide (CTAB) in 15 mL of deionized water to obtain solution B;
[0051] Solution A and solution B were mixed and stirred at room temperature for 60 min to obtain solution C;
[0052] Solution C was completely transferred to a microwave reactor with a polytetrafluoroethylene liner for microwave reaction at a reaction temperature of 170°C for 30 minutes. After the reaction was completed, the white product in the reactor was transferred to a centrifuge tube, washed and centrifuged with deionized water and anhydrous ethanol for multiple times, and then the product was dried in a drying oven at 60°C overnight to finally obtain zinc oxide nanorods.
[0053] The preparation of the zinc oxide-zinc sulfide composite piezoelectric catalyst is the same as the steps in Example 1.
[0054] The piezoelectric catalytic hydrogen production step is the same as that in Example 1. The gas chromatography test results show that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst is 1602 μmol / g.
[0055] Example 4
[0056] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0057] The applications of piezoelectric catalytic hydrogen production are as follows:
[0058] 100 mg of zinc oxide-zinc sulfide composite catalyst was placed in a two-way sealed sampling bottle containing triethanolamine and deionized water. The reactor was vented with nitrogen for 30 minutes. Then, the reactor was placed in an ultrasonic cleaner (40 kHz, 100 W) for piezoelectric hydrogen evolution reaction. The hydrogen content in the sealed reactor was detected every hour.
[0059] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1463 μmol / g.
[0060] Example 5
[0061] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0062] The applications of piezoelectric catalytic hydrogen production are as follows:
[0063] 100 mg of zinc oxide-zinc sulfide composite catalyst was placed in a two-way sealed sampling bottle containing lactic acid and deionized water. The reactor was vented with nitrogen for 30 minutes. Then, the reactor was placed in an ultrasonic cleaner (40 kHz, 100 W) for piezoelectric hydrogen evolution reaction. The hydrogen content in the sealed reactor was detected every hour.
[0064] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1569 μmol / g.
[0065] Example 6
[0066] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0067] The applications of piezoelectric catalytic hydrogen production are as follows:
[0068] 100 mg of zinc oxide-zinc sulfide composite catalyst was placed in a two-way sealed sampling bottle containing methanol and deionized water. The reactor was vented with nitrogen for 30 minutes. Then, the reactor was placed in an ultrasonic cleaner (40 kHz, 100 W) for piezoelectric hydrogen evolution reaction. The hydrogen content in the sealed reactor was detected every hour.
[0069] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1625 μmol / g.
[0070] Example 7
[0071] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0072] The applications of piezoelectric catalytic hydrogen production are as follows:
[0073] Take 100 mg of zinc oxide-zinc sulfide composite catalyst and put it into a two-way closed sampling bottle containing Na2S / Na2SO3 solution and deionized water. Use nitrogen to exhaust the reactor for 30 minutes. Then, place the reactor in an ultrasonic cleaner (40kHz, 110W) for piezoelectric hydrogen evolution reaction, and detect the hydrogen content in the closed reactor every hour.
[0074] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1736 μmol / g.
[0075] Example 8
[0076] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0077] The applications of piezoelectric catalytic hydrogen production are as follows:
[0078] Take 100 mg of zinc oxide-zinc sulfide composite catalyst and put it into a two-way closed sampling bottle containing Na2S / Na2SO3 solution and deionized water. Use nitrogen to exhaust the reactor for 30 minutes. Then, place the reactor in an ultrasonic cleaner (40kHz, 120W) for piezoelectric hydrogen evolution reaction, and detect the hydrogen content in the closed reactor every hour.
[0079] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1745 μmol / g.
[0080] Example 9
[0081] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0082] The applications of piezoelectric catalytic hydrogen production are as follows:
[0083] Take 100 mg of zinc oxide-zinc sulfide composite catalyst and put it into a two-way closed sampling bottle containing Na2S / Na2SO3 solution and deionized water. Use nitrogen to exhaust the reactor for 30 minutes. Then, place the reactor in an ultrasonic cleaner (40kHz, 130W) for piezoelectric hydrogen evolution reaction, and detect the hydrogen content in the closed reactor every hour.
[0084] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1802 μmol / g.
[0085] Example 10
[0086] The preparation steps of the zinc oxide-zinc sulfide composite piezoelectric catalyst are the same as those in Example 1.
[0087] The applications of piezoelectric catalytic hydrogen production are as follows:
[0088] Take 100 mg of zinc oxide-zinc sulfide composite catalyst and put it into a two-way closed sampling bottle containing Na2S / Na2SO3 solution and deionized water. Use nitrogen to exhaust the reactor for 30 minutes. Then, place the reactor in an ultrasonic cleaner (40kHz, 140W) for piezoelectric hydrogen evolution reaction, and detect the hydrogen content in the closed reactor every hour.
[0089] The gas chromatography test results showed that the 5-hour piezoelectric catalytic hydrogen evolution rate of the zinc oxide-zinc sulfide composite catalyst was 1783 μmol / g.
[0090] In the above embodiment, the concentration of solution A is 0.1-0.3 mol / L, and the concentration of solution B is (2-4)×10 -3 mol / L, solution C is at least 30mL, microwave reaction temperature range is 140-170°C, microwave reaction time is 30-60min. The above-determined specific drug amount, reaction temperature and time are the preferred values obtained by comparison within the given range.
[0091] We conducted a longitudinal comparison of the piezoelectric catalytic hydrogen evolution performance of the zinc oxide-zinc sulfide composite material in the present invention, and found that under the same ultrasonic power, when Na2S / Na2SO3 was selected as the hole capture agent, the piezoelectric catalytic hydrogen evolution performance of the zinc oxide-zinc sulfide composite material was the best; when Na2S / Na2SO3 was selected as the hole capture agent, it was observed that the piezoelectric catalytic hydrogen evolution performance of the zinc oxide-zinc sulfide composite material showed a parabolic trend with the increase of ultrasonic power. When the ultrasonic power was 130W, the piezoelectric hydrogen evolution performance of the composite material was the best, and its piezoelectric catalytic hydrogen evolution rate could reach 1802μmol / g, and the average hydrogen evolution rate was 360.4μmol / g / h. In addition, we also compared the piezoelectric catalytic hydrogen evolution activity of the composite catalyst of the present invention with that of the currently reported piezoelectric materials. For example, when the ultrasonic power was 100 W and the hole trapping agent was Na2SO3, the average hydrogen evolution rate of the BiFeO3 catalyst was 124.1 μmol / g / h; when the ultrasonic power was 100 W and the hole trapping agent was C6H 15When the ultrasonic power was 150W and the hole trapping agent was Na2S / Na2SO3, the average hydrogen evolution rate was 157.0μmol / g / h; when the ultrasonic power was 2W and the hole trapping agent was methanol, the average hydrogen evolution rate of the BiFeO3@COF catalyst was 180.7μmol / g / h; when the ultrasonic power was 2W and the hole trapping agent was methanol, the average hydrogen evolution rate of the Au / Bi4Ti3O 12 When the ultrasonic power of the catalyst is 200W and the hole capture agent is deionized water, the average hydrogen evolution rate is 194.6μmol / g / h, while the average hydrogen evolution rate of the zinc oxide-zinc sulfide composite piezoelectric catalyst in the present invention reaches 360.4μmol / g / h, showing the excellent piezoelectric catalytic performance of the composite material.
[0092] Cyclic stability test of zinc oxide-zinc sulfide composite piezoelectric catalyst:
[0093] The stability of a catalyst is directly related to its potential application value, so the present invention explores the stability of a zinc oxide-zinc sulfide composite piezoelectric catalytic material.
[0094] The optimal piezoelectric catalytic hydrogen evolution experimental conditions were selected, namely Na2S / Na2SO3 as hole capture agents and an ultrasonic power of 130W. The zinc oxide-zinc sulfide composite material was subjected to 15 cyclic hydrogen evolution tests, with each test lasting 5 hours. After each hydrogen evolution test, the catalyst was washed (using deionized water and alcohol), centrifuged, and dried for the next use.
[0095] The test results are shown in Table 1. After 50 hours of circulation, the average yield of piezoelectric catalytic hydrogen evolution of the zinc oxide-zinc sulfide composite piezoelectric catalytic material only decreased by 12.2% and gradually stabilized.
[0096] Table 1 Cyclic stability test performance table
[0097]
[0098] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a zinc-based composite piezoelectric catalyst, characterized in that: The following steps are included: Step 1: Preparation of ZnO nanorods 1) adding zinc acetate dihydrate into deionized water and stirring to obtain solution A; 2) dissolving hexadecyl dimethyl ammonium bromide in water to obtain solution B; 3) Mix solution A and solution B, and stir them thoroughly at room temperature to obtain solution C; 4) Completely transferring solution C to a microwave reactor lined with polytetrafluoroethylene for microwave reaction. After the reaction is completed, the white product in the reactor is transferred to a centrifuge tube, washed and centrifuged with deionized water and anhydrous ethanol for multiple times, and then the product is dried in a drying oven to finally obtain zinc oxide nanorods; Step 2: Preparation of zinc oxide-zinc sulfide composite piezoelectric catalyst 1) adding the zinc oxide nanorods prepared above into thiourea solution and stirring to obtain a white suspension; 2) Transfer the white suspension to an oil bath, heat it, and stir it thoroughly; 3) After the reaction is completed, the mixture is cooled and post-treated to finally obtain a zinc oxide-zinc sulfide composite piezoelectric catalyst.
2. The method for preparing the zinc-based composite piezoelectric catalyst according to claim 1, characterized in that: In step 1, the concentration of solution A is 0.1-0.3 mol / L, and the concentration of solution B is (2-4)×10 -3 mol / L, the microwave reaction temperature range is 140-170℃, and the microwave reaction time is 30-60min.
3. The method for preparing the zinc-based composite piezoelectric catalyst according to claim 2, characterized in that: In the step 2, the concentration of the thiourea solution is 0.05 M, and the oil bath heating temperature is 60-80°C.
4. The method for preparing the zinc-based composite piezoelectric catalyst according to claim 2, characterized in that: In the step 2, the post-treatment includes multiple centrifugal washings using deionized water and anhydrous ethanol respectively, and after the centrifugation, the obtained sample is placed in a constant temperature drying oven for drying.
5. Application of a zinc-based composite piezoelectric catalyst in piezoelectric catalytic hydrogen production, characterized in that: The following steps are included: The zinc oxide-zinc sulfide composite catalyst was placed in a two-way sealed sampling bottle containing a hole capture agent and deionized water, and exhaust treatment was performed for more than 30 minutes. Then, the reactor was placed in an ultrasonic cleaner to perform piezoelectric hydrogen evolution reaction.
6. The use of the zinc-based composite piezoelectric catalyst in piezoelectric catalytic hydrogen production according to claim 5, characterized in that: The hole capture agent is Na2S / Na2SO3 solution, lactic acid, triethanolamine or methanol.
7. The use of the zinc-based composite piezoelectric catalyst in piezoelectric catalytic hydrogen production according to claim 5, characterized in that: The power of the ultrasonic cleaner is 100W-140W.
8. The use of the zinc-based composite piezoelectric catalyst in piezoelectric catalytic hydrogen production according to claim 5, characterized in that: The exhaust gas treatment uses inert gas.
Citation Information
Cited By
A nitrogen-doped zinc sulfide piezocatalyst rich in sulfur vacancies and a preparation method and application thereof
CN122702472A